Nursing Handovers in Critical Care: A Retrospective Analysis of Information Content and Function. Issue 1 (September 2019) - Patterson, Emily S.; McIntire, Anne; Beecroft, Nicholas; Happ, Mary Beth; Moffatt-Bruce, Susan D.
Translating validated handover protocols from physicians in non-critical care settings to nursing report in critical care is challenging. Our objectives are to identify information content in verbal reports, where information is documented, and the function of non-documented communication. This is a descriptive study of 20 reports describing 27 patients from two medical intensive care units. Analysis involved unique coding of phrases and emergent themes analysis. Information categories included: Identify patient (51.9%); Narrative history (96.3%); Unusual symptoms (88.9%); Response to care (37%); Status of tasks (100%); Expectations of patients and families (55.6%). Information is documented in progress notes, the medication administration record, nursing flowsheets, lab results, orders, and past medical history. Information not typically documented supports providing patient-centered care, sharing clinical judgments, coordinating work, and mentorship. These objectives may guide nursing administrators in tailoring policies and procedures for nursing report to the needs of registered nurses in a critical care setting.